Nitric oxide as a signaling molecule in brassinosteroid‐mediated virus resistance to Cucumber mosaic virus in Arabidopsis thaliana - Zou, Li‐Juan; Deng, Xing‐Guang; Zhang, Li‐e; Zhu, Tong; Tan, Wen‐Rong; Muhammad, Arfan; Zhu, Li‐Jun; Zhang, Chao; Zhang, Da‐Wei; Lin, Hong‐Hui (Physiologia plantarum, 2018)
Brassinosteroids (BRs) are growth‐promoting plant hormones that play a crucial role in biotic stress responses. Here, we found that BR treatment increased nitric oxide (NO) accumulation, and a significant reduction of virus accumulation in Arabidopsis thaliana. However, the plants pre‐treated with NO scavenger [2‐(4‐carboxyphenyl)‐4,4,5,5‐tetramethyl‐imidazoline‐1‐1‐oxyl‐3‐oxide (PTIO)] or nitrate reductase (NR) inhibitor (tungstate) hardly had any NO generation and appeared to have the highest viral replication and suffer more damages. Furthermore, the antioxidant system and photosystem parameters were up‐regulated in brassinolide (BL)‐treated plants but down regulated in PTIO‐ or tungstate‐treated plants, suggesting NO may be involved in BRs‐induced virus resistance in Arabidopsis. Further evidence showed that NIA1 pathway was responsible for BR‐induced NO accumulation in Arabidopsis. These results indicated that NO participated in the BRs‐induced systemic resistance in Arabidopsis. As BL treatment could not increase NO levels in nia1 plants in comparison to nia2 plants. And nia1 mutant exhibited decreased virus resistance relative to Col‐0 or nia2 plants after BL treatment. Taken together, our study addressed that NIA1‐mediated NO biosynthesis is involved in BRs‐mediated virus resistance in A. thaliana.